Traditional Food Orem-Orem Photo Elements Effect on Malang Foodies Instagram Towards Teenage Purchase Intention - Ammamilha Rosyaqotut Saqufa; Bambang Dwi Prasetyo; Zulkarnain (International Journal of Science and Society, 2022)
Food photography is growing increasingly intense in a specific area of research today on the basis of the fast movement of information in micro media such as Instagram. Culinary activities, like drink or eat, are now not completely a physical need. Further, since the Instagram era, it becomes a self-representation canals to promotional activities. Refers to that acceleration, big oases just facing the almost-forgotten Malang traditional food like, orem-orem, so people, especially the youth one, can hear, reach, and spread the taste. This study aims to find out how the effect of orem-orem photo presentation on Malang Foodies Instagram towards the purchase intention of traditional food among teenage in Malang City. The research data conducted through explanative research using a quantitative approach. The theoretical framework of SOR (Stimulus-Organism-Response) and the classification of photographic element points helped to enrich research result. Shape, texture, pattern, form, and tone value become the main point of visual element that helped clarify visual description. The results showed that the photographic elements applied to orem-orem photos on Malang Foodies Instagram account had a positive and significant effect in activating emotional arousal and purchase intention among teenage. Furthermore, emotional arousal also has a significant influence in bridging photo elements to purchase intention.